Comparing Mutual Coupling of Ring Metamaterial on Square and Vivaldi Array Antennas - Petrus Kerowe Goran; Eko Setijadi (Buletin Pos dan Telekomunikasi, 2020)
The antenna performance is seen from the S-parameter value. The S-parameter graph can be seen as the return loss (S11, S22) and the mutual coupling (S21, S12) value. This research focuses on analyzing mutual coupling on Square and Vivaldi array antennas using the ring metamaterial method. The value of mutual coupling is considered very important to analyze because it affects the performance of the antenna in which is arranged in an array. The simulation results of the mutual coupling value obtained on a square array antenna use a ring metamaterial is -17 dB at a frequency of 2.4 GHz. Meanwhile, the Vivaldi array antenna uses a ring metamaterial that produces a mutual coupling value of -13.840744 dB at a frequency of 3.0162 GHz. The factors that affect the square array antenna so that it becomes the best to suppress the mutual coupling value between antenna elements are a selection of metamaterial shape and proper placement between the antenna array elements is arranged horizontally.